Aplikasi Pelaporan Data Quality Control Berbasis Android Menggunakan Metode Vaughan Dengan Memanfaatkan Sensor Geotgging Dan Kamera - Aris Priyanto; Hadi Zakaria (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
CV. Lintas Era Digital is a company engaged in the field of Technology Development Services in the world of Education which includes Hardware, Networking, Multimedia, Design, and Programming. The problem that is being experienced by CV. LINTAS DIGITAL ERA is a field control team in carrying out work where the owner wants to know in real terms the progress of the work, the location of the work, and the type of work that is currently underway in the field. Along with the development of today's technology, the author wants to make an Android-Based Quality Control Data Reporting Application Using the Vaughan Method By Utilizing Geotagging Sensors, Cameras, and Dropdown Chains. This application will be made using the PHP programming language (Hypertext Preprocessor) and for the server itself using XAMPP which consists of the Apache HTTP Server program, MySQL database, and language translator written in the PHP and Perl programming languages. with the framework from boostrap. With the Android-Based Quality Control Data Reporting Application using the Vaughan Method by Utilizing Geotagging Sensors and Cameras to make it easier for owners to monitor field teams, work locations, and work progress that is actually displayed on the application dashboard.